Endocytic activity in the thrombocytes of the turtle Phrynopys hilarii (freshwater South American species) - Pellizzon, Claudia H. [UNESP]; Lunardi, L. O. (My University, 2000)
The phagocytic process in cells depends on lysosomal enzymes, high-energy metabolism and cellular recognition. In this paper, we investigated the presence of energy and recognition factors in thrombocytes of turtle Phrynopys hilarii (a freshwater South American species). Turtle thrombocytes (P. hilarii) present glycogen - possibly β particles - dispersed in their cytoplasm and glycoproteins in the cell surface, as well as a large number of enzymes involved in the endocytic process (Pellizzon, 1996). The activity of these enzymes depends on high-energy metabolism and on cellular recognition provided by specific glycoconjugates (Alberts et al., 1994). This metabolic characterization is demonstrated by the large amount of glycogen particles observed in the cytoplasm by Thiéry's method. Glycogen labeling was also observed when concanavalin A-peroxidase was used as a marker for thrombocytes and for endocyted charcoal particles. Our results show that these cells have phagocytic ability, suggesting that their function in blood circulation is not limited to aggregation but may also involve a great potential for phagocytosis.
Keywords: Endocytic ability; Phrynopys hilarii; Thrombocytes; fresh water; glycogen; glycoprotein; animal; blood; electron microscopy; endocytosis; phagocytosis; physiology; South America; thrombocyte; turtle; ultrastructure; Animals; Blood Platelets; Endocytosis; Fresh Water; Glycogen; Glycoproteins; Microscopy, Electron; Phagocytosis; Turtles